2008
DOI: 10.1155/2008/173904
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns in the Management of Chronic Obstructive Pulmonary Disease in Primary Practice: The Cage Study

Abstract: Substantial gaps between recommended and current care exist in the management of COPD patients in primary care practice. Undertreatment of patients with severe COPD has potential clinical implications, including loss of autonomy and hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
116
7
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 15 publications
18
116
7
5
Order By: Relevance
“…Our data also indicate that only a minority of COPD patients in primary care are offered pulmonary rehabilitation advice or a referral for pulmonary rehabilitation, in line with data from other countries (13). The remarkably low documentation of self-management support and exacerbation-management or instruction with a written action plan is striking.…”
Section: Interpretation Of Findings In Relation To Previously Publishsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data also indicate that only a minority of COPD patients in primary care are offered pulmonary rehabilitation advice or a referral for pulmonary rehabilitation, in line with data from other countries (13). The remarkably low documentation of self-management support and exacerbation-management or instruction with a written action plan is striking.…”
Section: Interpretation Of Findings In Relation To Previously Publishsupporting
confidence: 83%
“…The documented counselling rate in the present study is much better than the 50% reported from former Swiss primary care data and is more in line with international benchmarks (8,13).…”
Section: Interpretation Of Findings In Relation To Previously Publishsupporting
confidence: 72%
See 1 more Smart Citation
“…However, the age, sex, and severity of COPD (according to the GOLD stage) of those patients who were included are comparable with the same characteristics of primary care patients with COPD who have participated in other studies. 22,23 To the authors' knowledge, this is the first study analysing changes in experienced personal and team continuity after the introduction of new care modes.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…Unfortunately, spirometry is significantly underutilized in primary care, with estimations of only about 50% to 60% of patients having had a single spirometry in the management of their asthma 1 or COPD. 2,3 Although the words are often used interchangeably, it is important to note that there is a difference between spirometry and pulmonary function testing (PFT). Spirometry is a diagnostic tool that can be performed anywhere by a properly trained health care professional.…”
Section: Introductionmentioning
confidence: 99%